An assessment of municipal solid waste management practices in Pulau Ketam Malaysia / Cao Xiang - Cao, Xiang (2016)
As a mangrove island, Pulau Ketam is rich in natural resources and attracts quite a number of visitors. Fishing and tourism are the main economic sources on this island. Therefore, municipal solid waste management in Pulau Ketam is becoming increasingly important. Presently, the total population is approximately 6 to 7 thousand on this island. Among them about 4 thousand residents are living in Pulau Ketam village, which is the study area. Through interviews, questionnaire, observation and document analysis, the information on current MSWM practices in Pulau Ketam was gathered. After 16 years of MSWM practice, the situation of management MSW has been changed. The solid waste collection company has placed dustbins on this island. However, open dumping on the island still exists. Throughout this study, an assessment has been done on the current status of MSWM practices in Pulau Ketam. This assessment has identified the issues of MSWM system, and subsequently proposed suggestions to overcome the issues. The major issues on this island are included: lack of infrastructures for MSWM system, weak awareness of islanders, and non-implementation government management policy. By analyzing and comparing with effective MSWM systems in Asia, especially Kamikatsu, appropriate sustainable solutions are proposed. The analysis proved that MSWM system cannot succeed without the understanding and commitment from the residents. Therefore, to overcome the issues, the committee of Pulau Ketam should set a program to increase islanders’ awareness of MSWM system, add the infrastructures of MSWM reasonable, and enforce the management of MSW recycling and disposal. Although achieving a successful MSWM system in Pulau Ketam has a long way to go, the islanders are certainly in a positive mindset to support any policy change towards cleaner home. Key words: Solid waste, MSW management, MSWM practice, Pulau Ketam.